2014
DOI: 10.1017/s0266467413000862
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in phyllostomid bat assemblages over a successional gradient in a tropical dry forest in southeastern Brazil

Abstract: 2014). Spatiotemporal variation in phyllostomid bat assemblages over a successional gradient in a tropical dry forest in southeastern Brazil . Abstract:The aim of this study was to investigate the spatiotemporal variation in richness, abundance, structure and composition of phyllostomid bats over a successional gradient in a tropical dry forest in south-eastern Brazil. Four successional stages (pasture, early, intermediate and late) were sampled in the northern part of the state of Minas Gerais. Bats were samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…A total of 84 bat species are currently reported for the state of Minas Gerais (Nogueira et al 2008, Tavares et al 2010, Gregorin & Loureiro 2011, Gregorin et al 2011b, Carvalho et al 2013, Falcã o et al 2014, Velazco et al 2014, Gregorin et al 2015, but only 19 are assigned to caatinga regions (Nogueira et al 2008, Tavares et al 2010, Falcã o et al 2014). The present results increase to 34 the number of bat species recorded for the caatinga of Minas Gerais, including T. saurophila, X. vieirai, and M. lavali, new records also for the state of Minas Gerais.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 84 bat species are currently reported for the state of Minas Gerais (Nogueira et al 2008, Tavares et al 2010, Gregorin & Loureiro 2011, Gregorin et al 2011b, Carvalho et al 2013, Falcã o et al 2014, Velazco et al 2014, Gregorin et al 2015, but only 19 are assigned to caatinga regions (Nogueira et al 2008, Tavares et al 2010, Falcã o et al 2014). The present results increase to 34 the number of bat species recorded for the caatinga of Minas Gerais, including T. saurophila, X. vieirai, and M. lavali, new records also for the state of Minas Gerais.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the material collected in Jaíba during the 1990s was listed by Tavares et al (2010) in a check list for the state of Minas Gerais, but more detailed information, including field observations, remain available only for a few taxa (Nogueira & Pol 1998, Nogueira et al 2003. In the most recent assessment of the bat diversity in northern Minas Gerais, Falcã o et al (2014) reported 22 species for the Mata Seca State Park, but no voucher material was prepared in this study. Herein we provide a revised list for the small mammals of Jaíba, including information on the sampling techniques, collection sites, taxonomy, and reproductive biology of selected species.…”
Section: Introductionmentioning
confidence: 99%
“…Either enhancement or decline in species richness can be anticipated. For example, a reduction of species richness was found by Avila-Cabadilla et al (2009), De la Peña et al (2012Falcão (2014); Vleut et al (2012Vleut et al ( , 2013. However, Bobrowiec and Gribel (2010) found similar bat richness in three types of secondary vegetation studied in Central Amazonia, but with different species composition in each vegetation type.…”
Section: Discussionmentioning
confidence: 93%
“…Bats are important bioindicators of tropical ecosystem health, as they play a key role in the ecological dynamics of forests, especially in pollination, and promotion of seed dispersal throughout the primary and secondary vegetation. These services extend even to open spaces as well as pastureland (Fenton et al 1992;Medellín et al 2000;Castro-Luna et al 2007;Melo et al 2009;García-Estrada et al 2012;Mass et al 2013;Avila-Cabadilla et al 2014;Voigt and Kingston 2016). Habitat loss and the resulting forest fragmentation are the major threats to Phyllostomid bats in the tropics.…”
Section: Introductionmentioning
confidence: 99%
“…In a broad context, we can state that the bat assemblage tends to be more diverse in preserved habitats and in environments with higher structural complexity [8][9][10]. However, little is known about habitat structure variables that cause those differences.…”
Section: Introductionmentioning
confidence: 99%